A novel high-strength and high-toughness dual-phase titanium alloy fabricated by CMT-DED - Zhenwen Chen; He Li; Zhen Wang; Cheng Xu; Xiaoyong Zhang; Jingjing Cheng; Jikang Fan; Jian Kong; Kehong Wang; Yong Peng (Virtual and Physical Prototyping)
This study introduces Ti6Al4V2Fe, a novel dual-phase titanium alloy, manufactured via Cold Metal Transfer Directed Energy Deposition (CMT-DED) for aerospace applications. This alloy meets stringent performance demands and enables efficient additive manufacturing of large-scale components. We investigated its microstructural evolution and mechanical properties under static and dynamic conditions. Room temperature tensile tests and dynamic impact assessments (1500/s to 3000/s) revealed a refined microstructure with short columnar and fine equiaxed prior-β grains, influenced by undercooling and thermal gradients. The addition of Fe enhanced β phase nucleation, resulting in a basket-weave α + β structure. Dynamic tests highlighted increasing strength with strain rate, with horizontal samples displaying superior strength. A constitutive model confirmed the experimental stress-strain profiles. At 2500/s, adiabatic shear bands indicated heightened sensitivity in horizontal samples, while vertical samples absorbed more energy, linked to dynamic recrystallization. The Ti6Al4V2Fe alloy, fabricated by CMT-DED, demonstrates remarkable strength, enhanced toughness, and reduced anisotropy, marking it as a prime candidate for aerospace applications.